2014
DOI: 10.3389/fpsyg.2014.00200
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-parietal and fronto-temporal theta phase synchronization for visual and auditory-verbal working memory

Abstract: In humans, theta phase (4–8 Hz) synchronization observed on electroencephalography (EEG) plays an important role in the manipulation of mental representations during working memory (WM) tasks; fronto-temporal synchronization is involved in auditory-verbal WM tasks and fronto-parietal synchronization is involved in visual WM tasks. However, whether or not theta phase synchronization is able to select the to-be-manipulated modalities is uncertain. To address the issue, we recorded EEG data from subjects who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 45 publications
(59 reference statements)
4
29
1
Order By: Relevance
“…In particular, theta rhythms in distributed brain regions are considered to interact with each other [7,8]. Moreover, it has been suggested that low-frequency synchronizations connect the frontal area with posterior sensory areas for the executive system [9,10,11]. However, network directionality of such interactions in WM is not clear; either top-down or bottom-up mechanisms which are defined as signals from sensory to frontal areas or signals from frontal to sensory areas, respectively in this study.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In particular, theta rhythms in distributed brain regions are considered to interact with each other [7,8]. Moreover, it has been suggested that low-frequency synchronizations connect the frontal area with posterior sensory areas for the executive system [9,10,11]. However, network directionality of such interactions in WM is not clear; either top-down or bottom-up mechanisms which are defined as signals from sensory to frontal areas or signals from frontal to sensory areas, respectively in this study.…”
Section: Introductionmentioning
confidence: 83%
“…were performed [10], and single-pulse TMS was delivered to three target areas (frontal area, visual area, auditory area). The tasks were also performed during sham-TMS and within a no-TMS condition.…”
Section: Introductionmentioning
confidence: 99%
“…Theta rhythms also have been shown to facilitate the formation of long-range functional networks, sometimes referred as theta synchronization (Buzsaki and Draguhn, 2004,Mellem, et al, 2013,von Stein and Sarnthein, 2000). During cognitive processing, including visual and auditory stimuli, theta synchronization/coupling helps in recruitment of various neural network and information co-ordination among distinct neuroanatomical structures (Kawasaki, et al, 2014). EEG studies in AD patients have also shown altered delta and theta power (Fraga, et al, 2013,Huang, et al, 2000,Jeong, 2004,van Deursen, et al, 2008), although they also exhibit a decrease in alpha and beta frequency band power (Fraga, et al, 2013,Jeong, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Shifts of attention to auditory objects held in working memory were associated with the activation of fronto-parietal attention systems, and further temporal and parietal activations distinguished between spatial and category-related attention cues ( Backer et al, 2015 ). Mental transformation and updating of auditory memory contents involved increased frontal and temporal theta power and enhanced fronto-temporal theta phase synchrony ( Kawasaki et al, 2010 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%